Empowering Local SMes: Unveiling Mienat Indonesia's Motivations and Strategies for Global Success - Sirodjudin, Mochamad; Mukhlis, Imam; Murwani, Fulgentius Danardana (PT FORMOSA CENDEKIA GLOBAL, 2024)
As the backbone of the national economy, SMEs hold immense potential to expand into international markets. The government's plan to elevate SMEs from domestic to international players underscores its commitment to empowering these businesses to reach a global audience. This qualitative descriptive study aims to explore the motivations driving SMEs to enter international markets and elucidate their internationalization strategies. Employing a case study approach, we delve into the experiences of Mienat Indonesia, a plant-based stick noodle brand venturing into the global snack industry. Interview transcripts were analyzed by segmenting them into units and explicating their connections to existing literature. The findings reveal a strong entrepreneurial spirit among SMEs, characterized by an international orientation and a firm commitment to expanding their businesses overseas.